Sea surface carbon dioxide at the Georgia time series site (2006–2007): Air–sea flux and controlling processes. (January 2016) - Xue, Liang; Cai, Wei-Jun; Hu, Xinping; Sabine, Christopher; Jones, Stacy; Sutton, Adrienne J.; Jiang, Li-Qing; Reimer, Janet J.
Highlights: The first full annual record of CO2 by MAPCO2 in the South Atlantic Bight. Time series CO2 controls were quantitatively identified using a 1-D model. River-influenced coastal system was vulnerable to terrestrial inputs. River inputs can induce CO2 interannual variability. Temporal under-sampling can greatly bias estimates of air–sea CO2 flux and NCP. Abstract: Carbon dioxide partial pressure ( p CO2 ) in surface seawater was continuously recorded every three hours from 18 July 2006 through 31 October 2007 using a moored autonomous p CO2 (MAPCO2 ) system deployed on the Gray's Reef buoy off the coast of Georgia, USA. Surface water p CO2 (average 373 ± 52 μatm) showed a clear seasonal pattern, undersaturated with respect to the atmosphere in cold months and generally oversaturated in warm months. High temporal resolution observations revealed important events not captured in previous ship-based observations, such as sporadically occurring biological CO2 uptake during April–June 2007. In addition to a qualitative analysis of the primary drivers of p CO2 variability based on property regressions, we quantified contributions of temperature, air–sea exchange, mixing, and biological processes to monthly p CO2 variations using a 1-D mass budget model. Although temperature played a dominant role in the annual cycle of p CO2, river inputs especially in the wet season, biological respiration in peak summer, and biological production during April–June 2007 also substantially influenced seawater p CO2 . Furthermore, sea surface p CO2 was higher in September–October 2007 than in September–October 2006, associated with increased river inputs in fall 2007. On an annual basis this site was a moderate atmospheric CO2 sink, and was autotrophic as revealed by monthly mean net community production (NCP) in the mixed layer. If the sporadic short productive events during April–May 2007 were missed by the sampling schedule, one would conclude erroneously that the site is heterotrophic. While previous ship-based p CO2 data collected around this buoy site agreed with the buoy CO2 data on seasonal scales, high resolution buoy observations revealed that the cruise-based surveys undersampled temporal variability in coastal waters, which could greatly bias the estimates of air–sea CO2 fluxes or annual NCP, and even produce contradictory results.